Development of Flip PDF-Based e-Booklet Learning Media on Indonesian Revolution Materials for Grade XI Students at SMA Negeri 6 Semarang - Kenanga Sari (Universitas Negeri Semarang, 2026)
The purpose of this study is to develop Flip PDF-based e-Booklet learning media, as well as to assess the feasibility of the media produced media. The method used is Research and Development (R&D) with a 4D development model consisting of Define, Design, Develop, and Disseminate stages, but the application is only in the Development stage. The research subjects consisted of 25 students in grades XI-L. Data collection techniques were carried out through interviews, observations, and questionnaire distribution. The results of the study show that Flip PDF-based e-Booklet learning media has a very high level of eligibility. This is shown by the validation results from media experts who reached 91% and material experts at 95%, both of which are included in the very feasible category. In addition, the results of the student response questionnaire showed a percentage of 83% which was also in the very good category. Thus, it can be concluded that the Flip PDF-based e-Booklet learning media on the Indonesian Revolution material is suitable for use as an alternative history learning media that is interactive, interesting, and able to increase students' interest and participation in learning activities.